Positive Selection and Inactivation in the Vision and Hearing Genes of Cetaceans. (3rd May 2020) - McGowen, Michael R; Tsagkogeorga, Georgia; Williamson, Joseph; Morin, Phillip A; Rossiter,; Stephen J
Abstract: The transition to an aquatic lifestyle in cetaceans (whales and dolphins) resulted in a radical transformation in their sensory systems. Toothed whales acquired specialized high-frequency hearing tied to the evolution of echolocation, whereas baleen whales evolved low-frequency hearing. More generally, all cetaceans show adaptations for hearing and seeing underwater. To determine the extent to which these phenotypic changes have been driven by molecular adaptation, we performed large-scale targeted sequence capture of 179 sensory genes across the Cetacea, incorporating up to 54 cetacean species from all major clades as well as their closest relatives, the hippopotamuses. We screened for positive selection in 167 loci related to vision and hearing and found that the diversification of cetaceans has been accompanied by pervasive molecular adaptations in both sets of genes, including several loci implicated in nonsyndromic hearing loss. Despite these findings, however, we found no direct evidence of positive selection at the base of odontocetes coinciding with the origin of echolocation, as found in studies examining fewer taxa. By using contingency tables incorporating taxon- and gene-based controls, we show that, although numbers of positively selected hearing and nonsyndromic hearing loss genes are disproportionately high in cetaceans, counts of vision genes do not differ significantly from expected values. Alongside these adaptive changes, we find increased evidence of pseudogenization of genes involved in cone-mediated vision in mysticetes and deep-diving odontocetes.